The Influence of Brand Image, Product Design, and Price on Purchasing Decisions for Nike Shoes in Denpasar City - Ni Wayan Jeni Kursita Yanti; I Gst. A. Kt. Gd. Suasana (International Journal of Asian Business and Management, 2024)
This consider points to decide the impact of brand picture, item plan and cost on acquiring choices. The area of this inquire about is in Denpasar City. The information collection method utilized was a survey. The populace employments Nike brand shoe items, with a test of 105 respondents. The data analysis techniques used are Descriptive Statistical Analysis, Data Instrument Test, Classical Assumptions, Multiple Linear Regression, F, t, Determination and Beta Coefficient. Based on the comes about of the think about, it was gotten that brand picture incorporates a positive and significant impact on obtaining choices, item plan incorporates a positive and noteworthy impact on acquiring choices, and cost incorporates a positive and critical impact on obtaining choices, brand picture, item plan and cost have a positive and noteworthy impact on obtaining choices. Suggestions that can be given by researchers are that it is hoped that Nike will always maintain the quality of the products offered, increase the variety of designs, so that later it will have products with a variety of designs, make more affordable pricing policies and add types of shoes, so that later it will have complete types of shoes